2017
DOI: 10.1038/srep41559
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila CG3303 is an essential endoribonuclease linked to TDP-43-mediated neurodegeneration

Abstract: Endoribonucleases participate in almost every step of eukaryotic RNA metabolism, acting either as degradative or biosynthetic enzymes. We previously identified the founding member of the Eukaryotic EndoU ribonuclease family, whose components display unique biochemical features and are flexibly involved in important biological processes, such as ribosome biogenesis, tumorigenesis and viral replication. Here we report the discovery of the CG3303 gene product, which we named DendoU, as a novel family member in Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 37 publications
(48 reference statements)
1
14
0
Order By: Relevance
“…Mouse EndoU has been reported to regulate peripheral B cell survival via reducing c-Myc mRNA level 25 . Inactivation of neuronal Drosophila DendoU causes neurotoxicity partially by downregulation of dTDP-43 26 . SARS and SARS-Covid-2 EndoU homologs Nps15/NendoU have been implicated in virus replication as well as limitation of host innate immune response, although the detailed functions are still enigmatic 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Mouse EndoU has been reported to regulate peripheral B cell survival via reducing c-Myc mRNA level 25 . Inactivation of neuronal Drosophila DendoU causes neurotoxicity partially by downregulation of dTDP-43 26 . SARS and SARS-Covid-2 EndoU homologs Nps15/NendoU have been implicated in virus replication as well as limitation of host innate immune response, although the detailed functions are still enigmatic 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The RNA-binding and endoribonuclease activities of EndoU family members were first shown in Xenopus by in vitro assays (Laneve et al, 2003;Renzi et al, 2006) and have since been confirmed in diverse organisms ranging from bacteria to humans (Ivanov et al, 2004;Laneve et al, 2008Laneve et al, , 2017Michalska et al, 2018;Poe et al, 2014;Schwarz and Blower, 2014;Ujisawa et al, 2018). EndoU family members appear to be involved in many aspects of biology, including small nucleolar RNA biogenesis (Renzi et al, 2006), endoplasmic reticulum (ER) network formation (Schwarz and Blower, 2014), immune response (Poe et al, 2014), neurodegeneration (Laneve et al, 2017), and viral replication (Ivanov et al, 2004), and as antibacterial toxins (Michalska et al, 2018;Zhang et al, 2011). Human EndoU, also known as PP11 (placental protein 11), has been suggested to be a tumor marker because it is expressed in various tumors despite having no detectable expression in tissues other than the placenta (Laneve et al, 2008).…”
Section: Endu-2 Is a Conserved Nuclease With Functions In Diverse Celmentioning
confidence: 98%
“…In Drosophila, DendoU has been found to be relevant for nervous system physiology and pathology. 9 The EndoU representatives are also present in prokaryotes, with the best characterized enzyme lacking uridylate specificity of the family and functioning as a tRNase toxin in bacterial communication. 10 In viruses, the NendoU protein is conserved among coronaviruses, arteriviruses, and toroviruses, but is absent in nonvertebrate-infecting representatives of the nidoviruses order: mesoniviruses and roniviruses.…”
Section: Introductionmentioning
confidence: 99%